Historia de la lectura en México (Colegio de México, Centro de Estudios Históricos, 1997)
This book is the result of the Seminar on the History of Education in Mexico, which takes place at El Colegio de México. Its purpose is to follow the evolution of reading -and, secondarily, also of writing- in our country: teaching methods, its role as a vehicle for ideologies, official campaigns, materials -magazines, newspapers, pamphlets and books- that over time have been offered to the curiosity of readers.